Identification of Dipeptidyl-Peptidase 4 (DPP-4) Inhibitors from Miracle Berry Fruit (Synsepalum dulcificum) Extract (Journal of Biochemistry, Microbiology and Biotechnology, 2023)
Dipeptidyl-peptidase 4 is a novel targeted enzyme in type 2 diabetes mellitus (T2DM) therapy due to its regulatory effect on incretin; glucagon-like peptide 1 (GLP-1) that responsible for stimulating insulin and suppressing glucagon secretion. DPP-4 degrades GLP-1 to biologically inactive fragments. In incretin-based therapies, DPP-4 inhibitor helps to restrain the inactivation of GLP-1, which in turn prolonging GLP-1’s half-life in blood and subsequently reducing the blood sugar more effectively. Nowadays, researchers are focusing to replace the synthetic drugs with natural-based drugs since they exert less toxicity. In our attempt to discover the natural inhibitor for DPP-4, miracle berry fruit was sequentially extracted with different solvents such as hexane, dichloromethane, chloroform, ethyl acetate and methanol and screened for the DPP-4 inhibitory activity. The analyses on the extractions show dichloromethane yielded the highest number of phenolic compounds with 38.37 mg GAE/g, while the highest number of flavonoids was found in hexane extract with 142.269 mg QE/g. On the other hand, qualitative analyses showed that methanol was able to extract alkaloids, terpenoids, saponins, tannins, quinones and carbohydrate from miracle berry fruit. It was also found that ethyl acetate extract was able to completely inhibit the enzyme. For further identification of constituent responsible for DPP-4 inhibitory activity, ethyl acetate extract was then subjected to silica gel column chromatography and eluted with different solvents with increasing polarity. The active fraction was then subjected to LC-MS/MS analysis and the results show it contains astragalin, nialamide, n-acetyl-l-phenylalanine, (+)-6-gingerol, 9-nitro oleate and 4(3H)-quinazolinone. The study indicates that miracle berry fruit extract contains natural DPP-4 inhibitor that can potentially be used for treating T2DM.